Analisis Budaya Kemandirian di Pesantren dari Perspektif Sosiologi Pendidikan - Sibarani, Nurhasanah; Eka Septiana; Muhammad Iqbal (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze in depth the cultural construction of independence in Islamic boarding schools through the perspective of educational sociology. The main focus of this study is to explore how social structures, power relations between kyai and santri, and hidden curriculum mechanisms contribute significantly to the formation of santri's independent character. This research is motivated by the discrepancy between national educational goals and the reality of the crisis of independence often found in formal educational institutions. Using descriptive qualitative methods through a literature study and critical synthesis approach, this study examines the phenomenon of independence as a sociological product. The results of the study show that the independence of santri is not merely obedience to formal rules, but rather the result of the formation of internalized habitus through strict daily discipline and the accumulation of cultural capital transmitted by the figure of the kyai. These findings confirm that the charismatic relationship between kyai and santri serves as the main channel for transmitting the values of initiative and responsibility. Furthermore, the hidden curriculum manifested in the daily exemplary behavior of the kyai has proven to be more effective in shaping the autonomy of santri than conventional classroom instruction. The implications of this study confirm that the educational ecosystem model in Islamic boarding schools can serve as a strategic reference for modern educational institutions in overcoming the challenges of character degradation and independence among students in the contemporary era.